Δ133p53α and Δ160p53α isoforms of the tumor suppressor protein p53 exert dominant-negative effect primarily by co-aggregation - Liuqun Zhao; Tanel Punga; Suparna Sanyal (eLife, 2025)
p53 is a tumor suppressor protein with multiple isoforms with shared or specific functions. However, two of its isoforms, Δ133p53α and Δ160p53α, with large N-terminal deletions, can cause cancer. These isoforms exert a dominant-negative effect on full-length p53 (FLp53), although the precise molecular mechanisms are unknown. Here, we investigate the mechanisms of action of Δ133p53α and Δ160p53α isoforms using chromatin immunoprecipitation, luciferase expression, subcellular fractionation, immunofluorescence assays, and apoptotic caspase activity assay. Our study elucidates that these DNA-binding deficient p53 isoforms form hetero-tetrameric complexes with FLp53 and disrupt FLp53’s DNA binding and transcriptional activities when present in a higher proportion than FLp53 in the tetramer. However, these structurally unstable isoforms promote vigorous protein aggregation involving FLp53, disrupting its structure and sequestering it in the cytoplasmic and nuclear aggregates, thereby limiting its availability to function as a transcription activator protein. Thus, co-aggregation of Δ133p53α and Δ160p53α with FLp53, rather than hetero-tetramerization, is likely the primary factor contributing to their dominant-negative effect. Modulating the stability and aggregation of p53 isoforms could be a novel strategy for cancer therapy.